ETNOGRAFI KOMUNIKASI PADA TRADISI SIRIH TANYA DALAM ADAT PERNIKAHAN MASYARAKAT MELAYU DI KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU - Ade Irawan; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Sirih tanya tradition in Malay customary marriage in Rokan IV Koto District, is carried on from generation to generation which contains values and norms in Malay people's lives. Sirih tanya tradition is a procession of proposing a woman to use betel pat, because Malay people believe that by delivering betel pat in proposing is a form of seriousness of a man. This reseach aims to determine the ethnography of communication on the sirih tanya traditions in malay customary marriage in the Rokan IV Koto sub-district, Rokan Hulu district. To achieve these goals then questions are raised how communicative siuation on the sirih tanya traditions in malay customary marriage, communicative events on the sirih tanya traditions in malay customary marriage and communicative actions  on the sirih tanya traditions in malay customary marriage.The author uses qualitative research methods, with ethnographic communication approaches. The research location was in Rokan IV Koto sub-district, Rokan Hulu regency. The time of research in October 2019 to January 2020. The research subjects consisted of 11 people, determined using purposive techniques. The object of ethnography of communication on the sirih tanya tradition in malay customary marriage. Data collection techniques through observation, interviews and literature study. Test the validity of the data with triangulation techniques and extension of participation.Research results explain that communicative situation on the sirih tanya tradition in malay customary marriage in the Rokan IV Koto sub-distrct, Rokan Hulu district that is moadatkan tepak sirih tanya situation, mouluokan tepak sirih tanya situation and monoangkan tepak sirih tanya situation. Then, communicative events on the sirih tanya tradition in malay customari marriage in the Rokan IV Koto sub-distrct, Rokan Hulu district covering : event type, event topic, function and purpose, settings, participants, message form, message content, sequence of actions, rules of interaction and interpretation norms. Next, comunicative actions, ninik mamak really understands the values contained in the custom of marriage. The meaning and value of marriage will be lost if there is no traditional wedding ceremony in a culture. Keywords : Ethnography Of Communication, Sirih Tanya Tanya Tradition, Malay Wedding Custom.